2020
DOI: 10.1111/jbi.14025
|View full text |Cite
|
Sign up to set email alerts
|

Varying support for abundance‐centre and congeneric‐competition hypotheses along elevational transects of mammals

Abstract: Aim: Whether species are most abundant at their geographic range centre and increasingly rare towards range limits (the abundance-centre hypothesis, ACH) has weak empirical support in birds along elevational gradients. This may be due to empirical limitations-most studies do not capture the multi-faceted nature of elevational gradients or species interactions. We examine the ACH and an alternative that the abundance maximum of elevational sympatric congeners will occur at different elevations along a gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…First, species may be distributed unevenly across their geographical range, and abundance tends to be highest near the range centre (the ‘abundant centre’ hypothesis; Brown, 1995). However, the ‘abundant centre’ hypothesis may not apply to the elevational range, as recent studies in mountains found limited support (bird: Freeman & Beehler, 2018; mammal: Wen et al., 2021). Second, species range size in a specific region (or at a single site) and global range size is not necessarily correlated (McCain, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…First, species may be distributed unevenly across their geographical range, and abundance tends to be highest near the range centre (the ‘abundant centre’ hypothesis; Brown, 1995). However, the ‘abundant centre’ hypothesis may not apply to the elevational range, as recent studies in mountains found limited support (bird: Freeman & Beehler, 2018; mammal: Wen et al., 2021). Second, species range size in a specific region (or at a single site) and global range size is not necessarily correlated (McCain, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The hard elevational limit is likely to distort abundance profiles by compressing the upper half-range width of the high elevation species, and putting extra pressure on the lower half-range. If this compression cascades downwards through interspecies and intraspecies competition we should expect to see the observed relationship between asymmetry and elevation (Jankowski et al, 2010; Stanton-Geddes et al, 2012; Huntsman & Petty, 2014; Péron & Altwegg, 2015; Wen et al, 2020),. Our highest sampling transects are less than 2 km from the highest ridge and therefore may be close enough to feel the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant Centre Hypothesis (ACH), that the abundance peak of a species coincides with the centre of its distribution , is the most commonly tested macro-ecological pattern of the environment-abundance paradigm (Brown, 1984; Sagarin & Gaines, 2002a; Murphy et al, 2006; Rivadeneira et al, 2010; Fenberg & Rivadeneira, 2011; Baldanzi et al, 2013; Freeman, 2017; Pironon et al, 2017; Burner et al, 2019; Wen et al, 2020). Niche modeling went further to determine correlations between observed abundance and (a large number of) environmental variables (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) reported differences in results when testing a data set for small mammals at local and regional scales. The possible explanations for this difference are likely to be topographic variation, climate and interspecific interaction within the study areas (Wen et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Their analysis showed that variables such as dispersal distance, geographic coverage and environmental coverage of the data appear to be important in explaining the observed variation between different species native to Africa, Europe and Asia. Most recently, although the relative abundance of a small mammal in Central and Southwest China was shown to exhibit a unimodal symmetric pattern of distribution around the centre of the species' distribution, this model appeared only once among the twelve studied elevational gradients for all species (Wen et al, 2020). Interestingly, Wen et al…”
Section: Introductionmentioning
confidence: 97%